USABILITY ANALYSIS OF WEB-BASED ANIMAL ADOPTION SYSTEM TO INCREASE USER EXPERIENCE - Stella Kova; Adi Prehanto; Rangga Gelar Guntara (STMIK Royal, 2024)
Abstract: Usability testing of online animal adoption systems is important because it is not only related to the comfort and safety of users, but also to the welfare of the adopted animals. So far, usability testing of the animal adoption system on Eidos has not been carried out and there is a problem that there is confusion with the process flow in this animal adoption system. This usability testing uses the Heuristic Evaluation method and the System Usability Scale (SUS), which involves in-depth interviews to obtain results that are not only statistical assessments, but also deeper insights from the user's perspective. The results of the evaluation using Heuristic Evaluation obtained 59 problems, with an average severity rating of 3 or major, whose improvements have resulted in several draft design recommendations. The recommendation design has gone through final testing using the System Usability Scale (SUS) which managed to achieve a score of 78, or categorized as good, along with some minor critical feedback for system improvement. Therefore, users as a whole feel very satisfied in using the online adoption system from the results of the existing recommendation design. The implications of the resulting recommendation design have been tested for usability by three UI/UX design experts and users directly so that they can be used as a basis for developing a better online animal adoption system. Keywords: animal adoption system; heuristic; prototype; system usability scale; usability Abstrak: Pengujian usability sistem adopsi hewan secara online penting untuk diperhatikan karena tidak hanya berkaitan dengan kenyamanan dan keamanan penggunanya saja, tetapi juga meningkatkan kesejahteraan hewan yang diadopsi. Sejauh ini, pengujian usability dari sistem adopsi hewan pada Eidos masih belum dilakukan dan ditemukannya masalah bahwa adanya kebingungan dengan alur proses dalam sistem adopsi hewan ini. Pengujian usability ini menggunakan metode Heuristic Evaluation dan System Usability Scale (SUS), yang melibatkan in-depth interview untuk memperoleh hasil yang bukan hanya berupa penilaian statistik saja, melainkan juga wawasan yang lebih mendalam dari sudut pandang pengguna. Hasil evaluasi menggunakan Heuristic Evaluation mendapatkan 59 permasalahan, dengan rata-rata perhitungan severity rating sebesar tiga atau major, yang perbaikannya telah menghasilkan beberapa rancangan desain rekomendasi. Adapun desain rekomendasi tersebut telah melalui pengujian akhir menggunakan System Usability Scale (SUS) yang berhasil meraih skor sebesar 78, atau terkategori good, disertai beberapa umpan balik kritis yang bersifat minor untuk peningkatan sistem. Dengan demikian, pengguna secara keseluruhan merasa sangat puas dalam menggunakan sistem adopsi online dari hasil desain rekomendasi yang ada. Implikasi desain rekomendasi yang dihasilkan telah teruji kegunaannya oleh sebanyak tiga ahli UI/UX design dan pengguna secara langsung sehingga dapat digunakan sebagai landasan bagi pengembangan sistem adopsi hewan secara online yang lebih baik. Kata kunci: heuristik; kebergunaan; prototipe; sistem adopsi hewan; system usability scale